2015
DOI: 10.1021/acs.jpcc.5b07533
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional CdS-Sensitized Sea Urchin Like TiO2-Ordered Arrays as Efficient Photoelectrochemical Anodes

Abstract: We demonstrate the fabrication of a 3D ordered sea urchin like TiO 2 structure by combining colloidal spheres template, atomic layer deposition (ALD), and hydrothermal growth method. The 3D sea urchin like TiO 2 arrays as photoanode present improved photoelectrochemical performance in contrast to 2D TiO 2 hollow microspheres and 1D TiO 2 nanowires arrays. With CdS quantum dots sensitization, the sea urchin like TiO 2 array photoanode yields a photocurrent of 5.4 mA cm −2 at 0 V vs Ag/AgCl. The performance impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…Recently, 3D TiO 2 nanoflowers (NFs) or branched TiO 2 nanowires have gained great attention because of their lager specific area, good carrier transmission, and enlarged electrode/electrolyte interface . However, the PEC performance of 3D TiO 2 NFs is still limited by the narrow light absorption in ultraviolet region due to its wide band gap, which only holds a proportion of 4% in the whole solar spectrum . Meanwhile, there still exists high recombination of photogenerated electron‐hole pairs in pure 3D TiO 2 photoanodes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 3D TiO 2 nanoflowers (NFs) or branched TiO 2 nanowires have gained great attention because of their lager specific area, good carrier transmission, and enlarged electrode/electrolyte interface . However, the PEC performance of 3D TiO 2 NFs is still limited by the narrow light absorption in ultraviolet region due to its wide band gap, which only holds a proportion of 4% in the whole solar spectrum . Meanwhile, there still exists high recombination of photogenerated electron‐hole pairs in pure 3D TiO 2 photoanodes .…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 However, the PEC performance of 3D TiO 2 NFs is still limited by the narrow light absorption in ultraviolet region due to its wide band gap, which only holds a proportion of 4% in the whole solar spectrum. [6][7][8][9] Meanwhile, there still exists high recombination of photogenerated electronhole pairs in pure 3D TiO 2 photoanodes. 10,11 Til date, many methods have been investigated to solve the above-mentioned problems of TiO 2 -based photoanodes such as doping, 12 surface decoration with metal nanoparticle, 9 forming heterojunction, [13][14][15] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising approach used to achieve the aforementioned challenges requires the use of bio-friendly, clean, and abundant source of energy like solar energy using semiconductor catalysts. Previous reports have shown that better performance is achieved from the use of cadmium sulfide (CdS) [9,10] among all other narrow band gap semiconductors like CuTe [11], PbSe [12], PbS [13], CdSe [14], and InP [15]. Because the solar spectrum contains 5% UV light, 48% visible (Vis) light, and 44% near infrared light [5], it is a better option to narrow the wide band gap of metal oxide semiconductors so that one can use Vis light to activate the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, BiVO 4 semiconductor is particularly attractive because it has a narrow band gap of ≈2.4 eV, suitable conduction band (0 V vs reversible hydrogen electrode, RHE) and valence band edges, high water splitting efficiency, and good chemical stability. For instance, 1D nanorods, [25] 2D nanosheets, [26] 3D inverse opals, [27] 3D hierarchical structures, [28][29][30] and 3D brochosomes-like arrays [31] have been reported to enhance the light harvesting and charge transport performance. To address these problems, various strategies such as morphology design, element doping, host-guest heterojunctions and surface modifications are developed to enhance the performance.…”
mentioning
confidence: 99%